MON-015 Pregnancy Adapts Circadian Rhythms in the Reproductive Axis: Impact on Labor Regulating Drug Efficacy - Hoffmann, Hanne Mette (J Endocr Soc, 2020)
Molecular and behavioral timekeeping is regulated by the circadian system represented on the cellular level by clock transcription factors, including Period2 (PER2), Bmal1, Clock and Cry. These transcription factors drive a daily ~24h rhythm in gene expression leading to tissue specific receptor expression optimizing sensitivity to hormones and drugs dependent on the time of day. To synchronize circadian rhythms in the body to the time of day, the brain’s suprachiasmatic nucleus (SCN) translates environmental light information into neuronal and endocrine signals allowing circadian rhythm synchrony. Despite the critical role of circadian rhythms in fertility, it remains unknown how circadian rhythms change within reproductive tissues during pregnancy, and how these adaptations might impact drug efficacy. Monitoring wheel-running patterns in circadian PER2::luciferase (PER2::LUC) reporter mice, we confirmed that pregnancy is associated with reductions of activity and identified a correlation between delayed onset of behavioral activity during late pregnancy and ex vivo SCN PER2::LUC period, whereas no correlation between arcuate nucleus PER2::LUC rhythms was identified. The time of day of peak PER2::LUC expression provides a time-stamp as to the circadian phase of a tissue. Pregnancy impacted circadian synchrony in the reproductive axis, with the most dramatic change within the uterus. To understand how circadian rhythms responded to input during pregnancy, we performed a pharmacology study and found that circadian rhythm generation in the uterus responded differentially to hormones regulating pregnancy and labor depending on gestational age and the time of day of drug administration. To test for functional changes in uterine contraction capacity, we recorded ex vivo uterine contractions. Our preliminary data reveal a circadian change in uterine function in the mouse, which impacted labor regulating drug efficacy depending on the time of day. Together our data show that pregnancy is associated with behavioral changes in locomotor activity patterns, as well as adaptations in phase-relationships in reproductive tissues. Our chrono-pharmacology study indicates that a better understanding of labor-regulating drug efficacy can potentially allow increased efficacy of currently used drugs in the clinic to both induce labor as well as halt preterm labor.